Peran Koperasi Unit Desa Dalam Kegiatan Usaha Masyarakat - Donald Samuel Slamet Santosa; Ida Yuliana Putri (FIRM Journal of Management Studies, 2018)
Co-operation is one of solution in society development, because of its motto or goals: member’s wealth. As the organization that members-owner, many provits and benefits that achieved by co-operation may used by co-operation’s members. This research aim to analyzed the role of village unit co-operation in support sociecty’s business. This research is qualitative research . Data collected by semi structured interview and Focus Group Discussion, that validated by sources and technique triangulation. Data analyzed by interactive analysis model of Miles and Huberman. Results of this research is 2 main roles: direct role and indirect role. The direct role consist by: 1) kredit activity; 2) advisor and distributor of production equipment; 3) processing and marketing of product; 4) distributing and trading. Then, indirect roles consist by: 1) developing member potency and economic ability; 2) improving economic wealth and social; 3) improving living quality; 4) reducing unemployment and poverty; 5) reducing urbanization.